'Suffer the little children' national and international dimensions of child poverty and public policy - Yeakey, Carol Camp.; Richardson, Jeanita W., 1957-; Brooks-Buck, Judith (Amsterdam ; Boston : Elsevier JAI, 2006)
This volume examines the burden of poverty that children and young adults disproportionately share throughout the world. Contributions from international researchers examine some of the profound precursor issues that serve to inhibit the chances of children and young adults to education and social mobility in an international context. Issues such as housing and homelessness, family income, maternal and child health, child care, hunger, adolescent pregnancy, violence by and against children, the impact of war and famine, various forms of social deviance and early childhood education are investigated. The volume also examines the social, political and economic contexts in which poverty occurs, utilizing various theoretical perspectives by which to view issues such as human rights, social development and social cohesion in developing, emerging and transitional societies. Implicit thoughout the volume are the decisions and non-decisions of governments as they confront issues of growing poverty and the repercussions of that poverty for future generations.
America's shame : children living in the shadows of America's prosperity / Carol Camp Yeakey, Jeanita W. Richardson and Judith Brooks Buck -- Talking poverty : urban Scots and social deprivation / David Matheson -- Fenced into cycles of deprivation : orphans, their female carers and education in Malawi / Rob McBride -- Roma childhood in eastern Europe / Tamás Kozma, Gabriella Pusztai and Katalin Torkos -- Coming to America : dashed hopes and uncertain futures / Elavie Ndura -- The loss of identity and the underutilization of black children's educational potential : rethinking assimilation globally / Kassie Freeman -- Children and youth in poverty in Trinidad and Tobago : a lack of commitment in the midst of plenty / Frank C. Worrell -- The dilemma of child soldiering in sub-Saharan Africa / Kingsley Banya and Juliet Elu -- Violence, democracy and education : an analytic framework -- Jamil Salmi -- The reach and possibilities of educational reform for the rural poor in Mexico / Maria Teresa Tatto -- Poverty and education : Brazil's search for viable solutions? / Francis Musa Boakari -- Small hands : global dimensions of child labor and exploitation / Carol Camp Yeakey and Judith Brooks Buck -- Child protection and survival in southern Africa : focus on child welfare policy in Namibia / Rodney K. Hopson -- The health and cognitive consequences of international child poverty / Jeanita W. Richardson -- Juvenile institutionalization practices in India : a study of two institutions in Madras / Sesha Kethineni and Tricia Klosky -- Child poverty in Sierra Leone : vignettes from the Leonenet Street Children's Project / Samuel Hinton -- Stolen childhood : cultural constructions of "unmarried" pregnancy in Bangladesh / Margot Wilson -- The World Bank, NGOs and the state of development in sub-Saharan Africa : implications for alleviating poverty and advancing societal reform / Kingsley Banya -- Defeating the trends : in search of a better future / Ximena de la Barra.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Poor children -- Social conditions; Poverty -- International cooperation; Poor children -- Government policy; Poverty -- Government policy; Children's rights; Education; Education -- Research